2014
DOI: 10.1063/1.4894741
|View full text |Cite
|
Sign up to set email alerts
|

The underexpanded jet Mach disk and its associated shear layer

Abstract: High resolution planar particle image velocimetry is used to measure turbulent quantities in the region downstream of the Mach disk in an axisymmetric underexpanded jet issuing from a convergent nozzle. The internal annular shear layer generated by the slip line emanating from the triple point is shown to persist across multiple shock cells downstream. A triple decomposition based on Proper Orthogonal Decomposition shows that the external helical structure associated with the screech tone generated by the jet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
66
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 32 publications
16
66
2
Order By: Relevance
“…The normalized values of these transverse velocities (u/U 1 ) were higher for methane than for hydrogen. Therefore, it may be concluded that the concavity of the Mach disk is due to gradient of the transverse velocity component (see the lines of Z/D=1.8 for the transverse profiles of Figure 10), not directly by the initial expansion fans at the nozzle lip as suggested in [10]. In fact, by moving away from the nozzle centreline, the direction of the velocity vector produced by the transverse and axial velocity components would be more inclined with respect to the nozzle centreline.…”
Section: Near-nozzle Shock Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…The normalized values of these transverse velocities (u/U 1 ) were higher for methane than for hydrogen. Therefore, it may be concluded that the concavity of the Mach disk is due to gradient of the transverse velocity component (see the lines of Z/D=1.8 for the transverse profiles of Figure 10), not directly by the initial expansion fans at the nozzle lip as suggested in [10]. In fact, by moving away from the nozzle centreline, the direction of the velocity vector produced by the transverse and axial velocity components would be more inclined with respect to the nozzle centreline.…”
Section: Near-nozzle Shock Characteristicsmentioning
confidence: 99%
“…Similarly to [10,59], the transverse velocity graphs of Figure 10 show that just after the Mach disk location (Z/D≈1.9 and 1.85 for methane and hydrogen, respectively), at 2.0D downstream of the nozzle exit, the flow has a transverse velocity component towards the jet boundary (positive value of u/U 1 ). This was attributed to the relative concavity of the Mach disk (see Figure 9) due to the initial expansion fans at the nozzle lip [10]. However, after a radial distance of ~0.55D, the flow was turned inwards by passing through an oblique shock which was formed by the reflection of the shock at the triple point.…”
Section: Near-nozzle Shock Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations